Symptomatic Apical Periodontitis of the Mandibular First Molar with the Accessory Canal in the Furcation Area Mimicking Furcation Perforation - Alexei Bolyachin; Zurab Khabadze; Oleg Mordanov; Magomed Gasbanov; Takhir Teberdiev (Case Reports in Dentistry)
Apical periodontitis frequently presents as a chronic disease. To arrive at a true diagnosis, in addition to the clinical examination, it is mandatory to undertake radiographic examinations and evaluate the clinical presentation. Knowledge of the root canal morphology is a prerequisite for effective nonsurgical endodontic treatment. The internal morphological features of the pulp chamber are variable and complex. This case report describes the treatment and outcome of symptomatic apical periodontitis of a mandibular first molar with the accessory (chamber) canal. The applied treatment fully contributed to the periapical lesion regression as shown in the four-year recall periapical radiography.